Pharmacokinetics and Efficacy Assessment of Long‐Term Ivermectin Treatment in Canine Demodicosis: Drug Disposition and Clinical Outcomes Relationship - S. Martínez; M. J. Del Sole; L. Maté; S. Sánchez Bruni; A. Lifschitz; M. Ballent (Journal of Veterinary Pharmacology and Therapeutics, 2026)
ABSTRACT Canine demodicosis is an inflammatory skin disease caused by Demodex canis mites. While newer isoxazoline classes currently represent the standard of care where licensed and available, prolonged ivermectin treatment remains an effective and cost‐effective alternative under specific socioeconomic contexts or clinical challenges associated with specific presentations, such as refractory pododemodicosis. Prolonged ivermectin treatment remains the primary choice, especially in resource‐limited settings and certain disease presentations. The aim was to characterize the pharmacokinetics of ivermectin following the reference multi‐dose regimen in both healthy (simulated based on a single dose) and demodicosis‐infested dogs, and to correlate systemic ivermectin exposure with clinical efficacy. Six healthy dogs received a single oral dose of ivermectin (0.5 mg/kg), and their profiles were extrapolated to a 56‐day regimen, while six demodicosis‐infested dogs were treated for 56 days at the same dose rate. MDR1 genotyping was performed in infested dogs prior to treatment. Plasma ivermectin concentrations were quantified by HPLC. After 56 days, trough plasma concentration ( C min ) values increased 3.48‐fold, consistent with C max increments ( p > 0.05). Comparative concentration ratios were 2.04 in healthy and 2.56 in infested dogs, without statistical differences ( p > 0.05). Plasma concentration‐time curves showed similar profiles, with comparable C max and AUC 0‐24 values (3231 vs. 3074 ng·h/mL). The same trend was observed when ivermectin accumulated after long‐term exposure (AUC 0‐56 ) (315,476 vs. 294,442). Skin scrapings confirmed mite clearance in treated dogs by Day 56. These findings suggest that prolonged ivermectin administration is safe and effective for treating canine demodicosis.